MAKING ORGANIC SOLID SOAP FROM PALM OIL, OLIVE OIL, AND PURE COCONUT OIL (VCO) WITH COFFEE POWDER AND COFFEE AROMA: Laboratorium Pendidikan IPA - reica fadli (SEMESTA: Journal of Science Education and Teaching, 2023)
Soap is one of the essential needs in everyday life. A mixture of olive oil, virgin coconut oil (VCO), and palm oil can be processed into soap bars using the cold process method. This soap making process involves the saponification reaction of oils and fats with NaOH. Cooking oil, as one of the commonly used sources of fatty acids, also plays a role in soap making. This research aims to utilize natural ingredients such as palm oil, olive oil, and VCO (Virgin Coconut Oil) in the production of solid organic soap. In addition, this research also investigates the impact of adding coffee powder on the texture, color, and aroma of the soap produced. The main focus of this research was to create high-quality soaps from natural ingredients, especially coffee, with the aim of providing beauty benefits and improving skin smoothness. During the research, it was found that the soap hardens within 2 weeks, while the total saponification process time requires 4-6 weeks for the soap to be safe for use. The significance of this research lies in understanding the effect of the mixture of palm oil, olive oil, and VCO in making soap bars, as well as the effect of adding coffee powder extract. The results of the study are expected to provide in-depth insight into the optimal formulation to create quality solid organic soap.